Effects of dopant contents on structural, morphological and optical properties of Er doped Ga2O3 films. (February 2016) - Chen, Zhengwei; Wang, Xu; Noda, Shinji; Saito, Katsuhiko; Tanaka, Tooru; Nishio, Mitsuhiro; Arita, Makoto; Guo, Qixin
Abstract: We have investigated structural, morphological and optical properties of erbium (Er) doped Ga2 O3 films with different Er contents. All the films were deposited on sapphire substrates by pulsed laser deposition. Temperature insensitive pure green luminescence at 550 nm has been demonstrated from these films. No peak shift at 550 nm is found with temperatures ranging from 77 to 450 K. The intensity of the green emission decreases with the increase of temperature, and the normalized intensity of the Er doped Ga2 O3 films has a smaller variation with temperature compared to Er doped GaN films. These results indicate that Ga2 O3 is a good host material for Er and potentially for other rare earth elements. Highlights: Er doped Ga2 O3 films were deposited on sapphire substrates for the first time. Intense pure green emissions at 550 nm are clearly observed for the Er doped films. No peak shift at 550 nm is found with temperatures ranging from 77 to 450 K. The intensity of the Er doped Ga2 O3 films has a smaller variation with temperature compared to GaN.